One Size Fits All? The Portability of Macro-Appraisal by a Comparative Analysis of Canada, South Africa, and New Zealand - Roberts, John (Archivaria, 2001)
This article examines the methodology of macr o-appraisal in environments other than the Canadian context in which it was originally developed. It considers the suitability of the model for government archives in Canada, South Africa, and New Zealand. Macro-appraisal is discussed first as a theoretical framework and then as a response to practical difficulties arising from other approaches to appraisal. The change management issues surrounding the possible adoption of macro-appraisal in other jurisdictions are explored. The article suggests that both theory and practice need to be addressed when considering the adoption of new models. While local conditions need to be considered, the possible value of overseas innovations should not be ignored.